2017
DOI: 10.1002/chem.201605430
|View full text |Cite
|
Sign up to set email alerts
|

What a Difference a Methyl Group Makes: The Selectivity of Monoamine Oxidase B Towards Histamine and N‐Methylhistamine

Abstract: Monoamine oxidase (MAO) enzymes catalyze the degradation of a very broad range of biogenic and dietary amines including many neurotransmitters in the brain, whose imbalance is extensively linked with the biochemical pathology of various neurological disorders. Although sharing around 70 % sequence identity, both MAO A and B isoforms differ in substrate affinities and inhibitor sensitivities. Inhibitors that act on MAO A are used to treat depression, due to their ability to raise serotonin concentrations, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 78 publications
5
34
0
Order By: Relevance
“…Thus, the results demonstrated the molecular interpretation and identification of structural determinants for the substrate specificity of the MAO‐B enzyme. The study also confirmed the hydrophobic nature of the MAO‐B active site and substantiated the crucial function of residues Ile199, Leu171, and Leu328 in properly orienting substrates for the reaction …”
Section: Molecular Modeling Studies On Mao‐b and Its Inhibitorssupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, the results demonstrated the molecular interpretation and identification of structural determinants for the substrate specificity of the MAO‐B enzyme. The study also confirmed the hydrophobic nature of the MAO‐B active site and substantiated the crucial function of residues Ile199, Leu171, and Leu328 in properly orienting substrates for the reaction …”
Section: Molecular Modeling Studies On Mao‐b and Its Inhibitorssupporting
confidence: 60%
“…Per‐residue interaction energy decomposition analysis depicted that the residue Ile197 was found to contribute the most toward deprenyl binding to MAO‐B. In contrast, Tyr396 and Tyr433 contributed greater and improved binding of compound 258 to MAO‐B …”
Section: Molecular Modeling Studies On Mao‐b and Its Inhibitorsmentioning
confidence: 99%
“…The effect of the rest of the protein environment was considered with the CPCM implicit solvation model using a dielectric constant of ε = 4.0, as suggested by Himo and co-workers [28], and a dielectric constant of ε = 78.4 for the aqueous solution, all in line with our previous reports [13], where we also demonstrated that a potential increase in the former dielectric constant to ε = 20.0 lowers the accuracy of the obtained results and even predicts wrong trends among ligands. Additionally, in our experience, such a truncated cluster-continuum model of the entire protein turned very useful in rationalizing various aspects of the catalytic activity [29], selectivity [30] and inhibition [31] of the monoamine oxidase family of enzymes, and is broadly used by different groups to decipher various biological phenomena [32][33][34][35][36], which justifies its use here. We note in passing that, despite its practical usefulness, the proposed value of ε = 4 is, in some cases, apparently too small to prevent the proton transfer from protonated to anionic residues, which then occurred spontaneously during the geometry optimization, provided the involved pair is in close vicinity.…”
Section: Computational Detailsmentioning
confidence: 98%
“…In this way all of the reported computational data correspond to the gas-phase Gibbs free energies at a temperature of 298.15 K and a pressure of 1 atm. The choice of such a computational setup was prompted by our recent success in modeling the properties of gelator molecules [23] and metal binding affinities [24], as well as correctly reproducing thermodynamic and kinetic parameters of organic [25,26] and enzymatic [27] reactions. In order to circumvent problems with the flexibility of the investigated systems, we tried many different conformations in each studied case and report here the results corresponding to the most stable structures.…”
Section: Computational Detailsmentioning
confidence: 99%